Superinduction of the Dictyostelium discoideum cell surface cAMP receptor by pulses of cAMP. - Chisholm, R L (1987)
Extracellular cAMP plays a crucial role in regulating the developmental program of Dictyostelium discoideum, functioning as a chemotactic agent, as well as a signal that regulates expression of developmentally expressed genes. These activities appear to be mediated by a cell-surface receptor for cAMP. We have studied the regulation of this receptor in cells developed in starved suspension cultures exposed to 50 nM pulses of cAMP every 6 min. cAMP-pulsed cells display roughly 10-fold higher cAMP receptor levels than cells that developed on filters or that were starved in suspension without cAMP pulses. Based on saturation binding analysis, the superinduced binding activity represents an increase in receptor number, while receptor affinity for cAMP is unaffected. Photoaffinity labeling of superinduced cells results in specific labeling of the same molecules that are labeled in starved cells. This increased cAMP binding activity was also detected in membrane preparations from cAMP-pulsed cells. These results provide evidence for an unusual mode of receptor regulation: autogenous induction of the receptor by its ligand.